Het Italiaanse communisme. - Napolitano, Giorgio; Hobsbawm, Eric John; Scholten, Yvonne (Amsterdam : Van Gennep, 1976)
Bibliotheek François Vercammen
Nederlands
Monografie
Keywords: communisme; Italië